A comparison of the growth status, rainfall retention and purification effects of four green roof plant species. (15th January 2021) - Gong, Yongwei; Zhang, Xianwei; Li, Haiyan; Zhang, Xiaoran; He, Song; Miao, Yuhong
Abstract: Vegetation is a key component of green roofs and one of the most important factors affecting the rainfall quantity and quality of green roofs. Four plant species ( Sedum lineare Thunb., Sedum spurium 'Coccineum', Sedum aizoon L. and Sedum spectabile ) and two planting methods (single-plant and mixed-plant) were tested on extensive green roofs (EGRs) in 2019. Plant growth status (plant height and vegetation coverage), rainfall volume control, nutrient concentration and load reduction were used to analyse the impact of the situation and the different plant growth conditions. The results showed that the growth status of Sedum lineare Thunb., Sedum aizoon L. and Sedum spectabile was great, and the vegetation coverage was more than 95% in summer. Each EGR with different sedum species had strong rainfall retention effects. The average retention rates of Sedum spectabile, Sedum lineare Thunb, mixed plants, Sedum aizoon L. and Sedum spurium 'Coccineum' were 90.98% and 91.38%, 88.51%, 83.42% and 84.17%, respectively. The average total nitrogen (TN) and nitrate nitrogen (NO3 − -N) concentrations of Sedum lineare Thunb. were 13.77 mg/L and 7.64 mg/L, which were higher than those of other sedum species, and the average concentrations of ammonia nitrogen (NH4 + -N) and total phosphorus (TP) of mixed plants were 4.01 mg/L and 0.48 mg/L, which were higher than those of single plants. Different plant species had different effects on nutrient loads. The EGRs of single plants and mixed plants indicated sinks of TN and NH4 -N and sources of TP, but the performance of NO3 − -N was inconsistent. Comprehensively, Sedum lineare Thunb., Sedum aizoon L. and Sedum spectabile were suitable for the green roofs. This study provides scientific support for the green roofs' application of actual projects and has a strong reference value for the development of green infrastructure. Graphical abstract: Image 1